Self-adaptive simulation method for natural gas pipeline considering temperature and pressure compensations - Xiong YIN; Bo XU; Tianyao LIU; Kai WEN; Weihe HUANG; Jing GONG (You-qi chuyun)
Objective The digital and intelligent operation of natural gas pipeline networks has emerged as an inevitable trend, emphasizing the vital role of online simulation technology. Methods This study proposed a self-adaptive approach for the online simulation of natural gas pipelines, focusing on simulation model construction, real-time data processing, and the design of a temperature-pressure compensator. The objective is to address the core algorithm for online simulation, which is not disclosed in foreign commercial software. Firstly, based on the fundamental flow equation of pipelines, the finite volume method employing a staggered mesh was utilized for discrete solutions, and the line model concept was integrated into the equipment model to enhance the precision, uniformity, and expansibility of the flow simulation process in natural gas pipelines. Meanwhile, the 3 Times Standard Deviation-Moving Average Filtering (3σ-MAF) method was applied for the real-time processing of SCADA data, to facilitate the identification of abnormal values in sensor data and the reduction of measurement noise. Subsequently, the study on model self-adaption was transformed into an investigation into negative feedback control to minimize the discrepancy between measured and simulated values leveraging the control theory. Furthermore, a temperature-pressure compensator design was introduced, utilizing the Proportional Integral Derivative (PID) algorithm to enable the gas flow state correction in the online simulation process. The proposed algorithm was verified through its practical implementation in a real pipeline network scenario. Results In the comparison with the measured SCADA data, the average relative error between the simulated and measured data decreased from 2.407% to 0.066% following pressure correction, and from 1.525% to 0.273% due to temperature correction. These reductions underscored the significant effectiveness of enhancing the accuracy of online simulation results. Conclusion The proposed self-adaptive simulation method for natural gas pipelines considering temperature and pressure compensations, stands out for its stable algorithm, rapid error correction, and minimal convergence error. This method provides a theoretical foundation for the subsequent applications of domestic online simulation software at the industrial level.